Framing structure of the news of the new COVID-19 variant in 2025, in Kompas.com - Damayanti Wardyaningrum (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2024)
The mass media are expected to continue to play a role in educating the public about the development of the new variant of COVID-19 and its treatment. This study is conducted with the aim of obtaining an overview of how the framing built by the media Kompas.com in constructing ideas for the readers about the new variant of COVID-19. This research analysis uses Pan and Kosiscki’s framing, which consists of four structures. The results of the study find that the news is framed in the syntactic structure, and news leads are arranged from general to specific, starting with data about the increase in cases in three countries, to detailed information about the new variant. Moreover, source citations only come from the government, so the content of the news is not yet balanced. In the script structure, news is arranged by presenting the latest things that are considered important and new to the readers, followed by explanations and solutions. The thematic structure shows a selection of themes that attract the attention of readers but are deep with rationality. There are no nuances of overly emotional or sensational narrative. In the rhetorical structure, the emphasis on certain meanings in the news uses word choices that tend to be normative. The news writer employs idioms that are still felt general, with no specific emphasis. The construction of media framing is relatively reassuring to the public, who are still traumatised by the past pandemic.